Analysis of the Social Determinants of Entrepreneurial Intention among Sub-Saharan Students in Morocco - Naoual Farissi; Youssouf Meite (Journal of Social Entrepreneurship Theory and Practice, 2025)
This article is based on research on the socio-professional integration of sub-Saharan students in Morocco. It assesses the entrepreneurial intentions of these students at the end of their training cycle. To achieve this objective, we used two approaches and two tools to conduct this study. First, a sample survey using a questionnaire sent online. Second, the snowball technique, which allowed us to conduct individual interviews using an interview guide to obtain qualitative data, targeted at approximately thirty people selected based on recommendations. The sample survey achieved a sample of 200 people through saturation. The study indicates that personal and psychological factors determine the entrepreneurial intentions of sub-Saharan students in Morocco. Specifically, the results first reveal the influence of the Moroccan context in terms of training and investment opportunities. Next, the students' sociocultural environment and the mobilization of social (family) capital available in their region of origin are considered determinants of their desire to become entrepreneurs